Identification of medicinal plans used by residentes of the Serra Catarinense region (Research, Society and Development, 2020)
Objective: to identify the use of medicinal plants for the treatment and prevention of diseases used by residents of the AMURES region (Association of Municipalities in the Mountain Region). Methodology: a qualitative and quantitative exploratory descriptive research was carried out at the AMURES Health Consortium in Lages, SC, totaling one hundred interviews in total. Results: It was analyzed that 67% of the interviewees were female and 33% male. Medicinal plants were mentioned as a form of use due to family tradition by 43.6% of respondents. There were 200 quotes about who taught them to practice, with 32% citing that their grandparents taught them to practice. Respondents 75% stated that they taught their practices of using medicinal plants to their children. The medicinal plants most used by the interviewees were: marcela 11.41%, lemon balm 10.51%, mint 9.61%, wormwood 4.8%, artichoke 4.5%, chamomile 3.6%, of which 55.56 % were other plants. Of the interviewees, 94 people mentioned that they use medicinal plants in tea format, 5 use them on the skin and 1 mentioned that they use them on the scalp. Conclusion: With this, it was observed that the use of medicinal plants is still present by residents of the AMURES Region.